Preparation method of medical titanium alloy with compact surface layer and porous interior
Through the preparation method of Ti6Al4V5Cu medical titanium alloy with dense surface and porous internal porous, the problems of elastic modulus mismatch and lack of antibacterial properties of existing titanium alloy implant materials are solved, and the effects of high strength, low elastic modulus and antibacterial properties are achieved. Promotes bone tissue growth and acts as stress release and buffers when the material is deformed under stress.
Patent Information
- Application Number
- CN202411693967.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The intervertebral implant materials prepared from existing titanium alloys have problems with elastic modulus mismatch and lack of antibacterial properties, which leads to prone to problems such as bone implant instability and bacterial infection after surgery.
The surface-intensive internal porous Ti6Al4V5Cu medical titanium alloy preparation method is adopted to prepare spherical titanium alloy powder by electrode induction melting inert gas atomization method, and sintered by discharge plasma sintering technology to form a dense internal porous structure of surface layer.
It realizes a medical titanium alloy with high strength, low elastic modulus and antibacterial properties, and has an interconnected internal porous structure, which promotes the growth of bone tissue and plays a stress release and buffering role when the material is deformed under stress.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a medical titanium alloy with a dense surface and porous interior, and belongs to the field of biomedical materials. Background Art
[0002] An intervertebral implant is a medical implant used in spinal fusion surgery, mainly used to treat spinal diseases such as herniated disc, spondylolisthesis, spinal instability, scoliosis, spinal tumors, spinal infection or spinal fracture. Its main function is to fill the intervertebral space, provide support and stability, and promote bone fusion between adjacent vertebrae after removing the damaged intervertebral disc or vertebra. At present, the most commonly used Ti6Al4V alloy titanium cage for intervertebral implants has certain biocompatibility and stability, but due to the mismatch between the elastic modulus of Ti6Al4V alloy and human bone, it is easy to cause problems such as implant sinking and stress shielding in adjacent vertebrae after surgery. In addition, Ti6Al4V alloy does not have antibacterial properties and is prone to bacterial infection after surgery, which not only shortens the service life of the implant, but may also cause implant failure, causing great pain and economic burden to patients. A large number of studies have shown that by adding copper to the Ti6Al4V alloy, not only the strength and corrosion resistance of the alloy are improved, but also it is endowed with unique antibacterial capabilities. In particular, the Ti6Al4V5Cu alloy not only has good mechanical properties, but also has a killing rate of up to 98% against Staphylococcus aureus. Summary of the invention
[0003] In order to overcome the deficiencies of the prior art, especially the problems of elastic modulus mismatch and lack of antibacterial property in intervertebral implant materials made of existing titanium alloys, the present invention provides a method for preparing a medical titanium alloy with a dense surface and a porous interior.
[0004] The present invention is accomplished by the following technical scheme: a method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0005] (1) Using spherical Ti6Al4V5Cu titanium alloy powder with a particle size of 10 to 20 μm as raw material;
[0006] (2) adding the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder in an amount of 6.13-6.54 g / ml, heating to 20-30° C., stirring and mixing to obtain a mixture I for standby use;
[0007] (3) adding NH4HCO3 powder with a particle size of 300 to 500 μm and used as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1) at a mass ratio of 35 to 45%, mixing them evenly to obtain a mixture II for standby use;
[0008] (4) Filling the mixture I of step (2) into a stainless steel mold and pressing it into a hollow cylinder, then filling the mixture II of step (3) into the hollow cylinder, cold pressing and removing the mold to obtain a green body with the outer layer of the mixture I and the inner layer of the mixture II;
[0009] (5) placing the green body of step (4) into a tubular furnace, heating the body to 200-300° C. at a heating rate of 4-8° C. / min under a vacuum degree of 10-25 Pa and a continuous flow of 99.99% pure argon atmosphere, and keeping the temperature for 240-300 min to complete thermal debinding, followed by cooling to room temperature with the furnace for standby use;
[0010] (6) The green body after thermal degreasing in step (5) is placed in a graphite mold, placed in a spark plasma sintering furnace, evacuated to 4-6 Pa, heated to 550-650° C. at a heating rate of 80-90° C. / min, then heated to 850-900° C. at a heating rate of 90-110° C. / min, and finally heated to 1100-1200° C. at a heating rate of 40-50° C. / min, kept at this temperature for 8-12 min to complete spark plasma sintering, and then cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy with a dense surface and porous interior.
[0011] Preferably, the chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder in step (1) is as follows: Al: 5.50-6.50wt.%, V: 3.50-4.50wt.%, Cu: 4.50-6.0wt.%, Fe: ≤0.25wt.%, C: ≤0.08wt.%, N: ≤0.03wt.%, H: ≤0.008wt.%, O: ≤0.13wt.%, and the balance is Ti.
[0012] Preferably, the spherical Ti6Al4V5Cu titanium alloy powder in step (1) is prepared by electrode induction melting and inert gas atomization method.
[0013] Preferably, the pressing process of step (4) is unidirectional pressing, the pressing rate is 1 to 3 kN / min, the pressure is 45 to 50 kN, and the holding time is 25 to 30 min.
[0014] The stainless steel mold of step (4) includes: a sleeve with a base at the bottom and a vertical cavity therein, a cushion block is provided at the bottom of the vertical cavity, and also includes a fixed cylinder that can be placed in the vertical cavity of the sleeve, a core rod placed in the fixed cylinder, and a mold pressure rod that can be placed in the vertical cavity of the sleeve.
[0015] The graphite mold structure of step (6) is: a cylindrical shell with a cylindrical inner cavity, and plugs are respectively connected to both ends of the cylindrical shell.
[0016] The present invention has the following advantages and beneficial effects:
[0017] The Ti6Al4V5Cu medical titanium alloy with a dense surface and porous interior prepared by the above technical solution of the present invention has an interconnected internal porous structure while obtaining high strength, low elastic modulus and antibacterial properties, which can promote the growth of bone tissue. The spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method is used as a raw material, which has the advantages of high sphericity, good fluidity, high purity and low gas impurity content, and the pre-alloyed spherical Ti6Al4V5Cu titanium alloy powder is sintered by spark plasma sintering technology, which realizes precise control of elements and effectively avoids the segregation problem of the chemical composition of the sintered product. In addition, the use of pre-alloyed spherical Ti6Al4V5Cu titanium alloy powder significantly reduces the activation energy of metal atom diffusion, thereby reducing the sintering temperature and energy consumption, which helps to reduce costs. The prepared surface dense / internal porous medical titanium alloy has high compressive strength (≥872MPa) and low elastic modulus (≤16GPa), and the internal porous structure of the surface dense and internal porous medical titanium alloy is interconnected (porosity is 50% to 68%), which can not only promote the growth of bone tissue, but also release stress and buffer the motion load when the material is deformed. At the same time, copper ions (Cu + ) and body fluids can be transmitted between the internal porous structure and bone tissue, giving the alloy a certain antibacterial property. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a morphology diagram of the spherical Ti6Al4V5Cu titanium alloy powder used in the present invention;
[0019] Figure 2 A structural diagram of a stainless steel mold used in an embodiment of the present invention;
[0020] Figure 3 This is a schematic diagram of the pre-pressing process after powder filling of the present invention;
[0021] Figure 4 This is an interface morphology of a Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior prepared in Example 2 of the present invention;
[0022] Figure 5 The compressive strength-elastic modulus diagram of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior prepared in Examples 1, 2 and 3 of the present invention;
[0023] Figure 6 This is a compressive strength-elastic modulus diagram of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior prepared in Examples 2, 4 and 5 of the present invention.
[0024] Figure 2 Middle: 1-core rod; 2-fixed cylinder; 3-sleeve; 4-base at the lower end; 5-mold pressure rod, 6-pad at the bottom of the vertical cavity of the sleeve; DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific implementation methods, but the protection scope of the present invention is not limited to the above contents.
[0026] Example 1
[0027] A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0028] (1) Using spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method as raw material, the particle size of which is 10 μm;
[0029] The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder is as follows: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;
[0030] (2) adding 6.13 g / ml of the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder, heating to 20° C., stirring and mixing to obtain a mixture I for standby use;
[0031] (3) Add NH4HCO3 powder with a particle size of 300 μm and used as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1) at a mass ratio of 40%, mix well, and obtain mixture II for standby use; the purity of NH4HCO3 powder used as a pore-forming agent is analytical grade and the particle size is 300 μm;
[0032] (4) The stainless steel mold used in this step includes: a base 4 at the bottom, a sleeve 3 with a vertical cavity therein, a cushion block 6 at the bottom of the vertical cavity, a fixed cylinder 2 that can be placed in the vertical cavity of the sleeve 3, a core rod 1 placed in the fixed cylinder 2, and a mold pressing rod 5 that can be placed in the vertical cavity of the sleeve 3; during operation: the cushion block 6 is placed in the vertical cavity of the sleeve 3, the core rod 1 is inserted into the vertical cavity of the sleeve 3, and then the mixture I of step (2) is filled into the vertical cavity of the sleeve 3, and the fixed cylinder 2 is inserted, and the mixture inside is manually pressed. Ⅰ is pressed into a hollow cylinder, then the core rod 1 is pulled out, the mixture Ⅱ in step (3) is filled into the vertical cavity of the fixed tube 2, and the core rod 1 is inserted again. The core rod 1 is manually pressed to compact the mixture Ⅱ in the hollow cylinder, the core rod 1 and the fixed tube 2 are pulled out, and the mold pressure rod 5 is inserted, and then sent to a conventional press, and unidirectional pressure is applied to 45 kN at a pressure rate of 1 kN / min, and the pressure is maintained for 30 minutes to complete the cold pressing molding, and then demolding is performed to obtain a cylindrical green body with an outer layer of dense mixture Ⅰ and an inner core of porous mixture Ⅱ;
[0033] (5) placing the cylindrical green body of step (4) into a tubular furnace, heating the body to 250° C. at a rate of 5° C. / min under a vacuum degree of 10 Pa and a continuous flow of 99.99% pure argon atmosphere, and maintaining the temperature for 280 min to complete thermal debinding, followed by cooling to room temperature in the furnace for standby use;
[0034] (6) placing the cylinder that has been thermally degreased in step (5) into a graphite mold, and then placing it in a spark plasma sintering furnace. After evacuating to 5 Pa, heating it to 590° C. at a heating rate of 85° C. / min, then heating it to 880° C. at a heating rate of 100° C. / min, and finally heating it to 1200° C. at a heating rate of 45° C. / min, keeping the temperature for 10 min, completing spark plasma sintering, and then cooling it to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior;
[0035] The graphite mold structure is: a cylindrical shell with a cylindrical inner cavity, and plugs are respectively connected to both ends of the cylindrical shell.
[0036] The dimensions of the cold-pressed green body and the sintered sample were measured using a vernier caliper, and the shrinkage of the sample was obtained using a conventional calculation formula; the radial shrinkage and axial shrinkage of the Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior were 12.10% and 10.87%, respectively.
[0037] The dense layer and the porous layer were cut into 3mm×3mm×3mm samples by electric spark wire cutting, and polished with 400 mesh sandpaper to expose the surface with metallic luster. The density of the dense layer and the porosity of the porous layer were measured according to the Archimedes drainage method. The density of the surface dense layer of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior was 93.1%, and the porosity of the internal porous layer was 58.5%.
[0038] The mechanical properties of the material were tested for compression properties according to GB / T 31930-2015. In order to make the test statistically significant, the average value was taken after multiple tests. The test results are shown in Figure 5 The Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and porous interior has high compressive strength and a low elastic modulus. The compressive strength is 1104MPa, the yield strength is 775.9MPa, and the elastic modulus is 15.1GPa, which has an elastic modulus matching that of human bones (2-30GPa). After implantation, it has both load-bearing capacity and can disperse stress, reduce stress shielding, and is conducive to long-term and effective implantation.
[0039] Example 2
[0040] A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0041] (1) Using spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method as raw material, the particle size of which is 10 μm;
[0042] The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder is as follows: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;
[0043] (2) adding 6.13 g / ml of the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder, heating to 20° C., stirring and mixing to obtain a mixture I for standby use;
[0044] (3) Add 40% by mass of NH4HCO3 powder with a particle size of 300 μm as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1), mix well, and obtain mixture II for standby use; the purity of the NH4HCO3 powder used as a pore-forming agent is analytical grade;
[0045] (4) The stainless steel mold used in this step is the same as that in Example 1; the cushion block 6 is placed in the vertical cavity of the sleeve 3, the core rod 1 is inserted into the vertical cavity of the sleeve 3, and then the mixture I of step (2) is filled into the vertical cavity of the sleeve 3, the fixed cylinder 2 is inserted, and the mixture I therein is pressed manually to be pressed into an internal hollow cylinder, then the core rod 1 is pulled out, and the mixture II of step (3) is filled into the vertical cavity of the fixed cylinder 2, and the core rod 1 is inserted again, and the core rod 1 is pressed manually to compact the mixture II into the hollow cylinder, the core rod 1 and the fixed cylinder 2 are pulled out, and the mold pressure rod 5 is inserted, and then sent to a conventional press, and unidirectionally pressurized to 50 kN at a pressurization rate of 2 kN / min, and the pressure is maintained for 25 minutes to complete the cold pressing molding, and then demolded to obtain a cylindrical green body with a dense outer layer of the mixture I and a porous inner core of the mixture II;
[0046] (5) placing the cylindrical green body of step (4) into a tubular furnace, heating the body to 200° C. at a rate of 4° C. / min under a vacuum degree of 15 Pa and a continuous flow of 99.99% pure argon atmosphere, and maintaining the temperature for 260 min to complete thermal debinding, followed by cooling to room temperature in the furnace for standby use;
[0047] (6) The cylinder that has been thermally degreased in step (5) is placed in a graphite mold, and then placed in a spark plasma sintering furnace. After evacuating to 5 Pa, the temperature is increased to 650°C at a heating rate of 90°C / min, and then increased to 850°C at a heating rate of 90°C / min. Finally, the temperature is increased to 1150°C at a heating rate of 50°C / min, and kept at this temperature for 12 minutes to complete the spark plasma sintering. The cylinder is then cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior. The graphite mold structure is the same as that in Example 1.
[0048] The dimensions of the cold pressed green body and the sintered sample were measured with a vernier caliper, and the shrinkage of the sample was obtained using a conventional calculation formula. The radial shrinkage and axial shrinkage of the Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and porous interior were 11.9% and 10.48% respectively.
[0049] The dense layer and the porous layer were cut into 3mm×3mm×3mm samples by electric spark wire cutting, and polished with 400 mesh sandpaper to expose the surface with metallic luster. The density of the dense layer and the porosity of the porous layer were measured according to the Archimedes drainage method. The density of the surface dense layer of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior was 92.5%, and the porosity of the internal porous layer was 61.0%.
[0050] The Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior obtained in Example 2 was observed by metallographic microscope. Figure 3As shown in the figure, it can be seen that the interface between the dense layer and the porous layer is well-proportioned, the structure is uniform, and no cracks are generated. The porous layer forms uniformly distributed pores of different sizes due to the volatilization of the pore-forming agent NH4HCO3, and the pore size is mainly distributed between 200 and 700um, which meets the requirements for bone cell growth.
[0051] The mechanical properties of the material were tested for compression properties according to GB / T 31930-2015. In order to make the test statistically significant, the average value was taken after multiple tests. The test results are shown in Figure 5 The Ti6Al4V5Cu medical titanium alloy with dense surface and porous interior has high compressive strength and low elastic modulus, with a compressive strength of 1040.2MPa, a yield strength of 762.9MPa, and an elastic modulus of 14.6GPa, which matches the elastic modulus of human bones (2-30GPa). After implantation, it has both load-bearing capacity and can disperse stress, reduce stress shielding, and is conducive to long-term and effective implantation.
[0052] Example 3
[0053] A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0054] (1) Using spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method as raw material, the particle size of which is 15 μm;
[0055] The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder is as follows: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;
[0056] (2) adding 6.34 g / ml of the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder, heating to 25° C., stirring and mixing to obtain a mixture I for standby use;
[0057] (3) Add 40% by mass of NH4HCO3 powder with a particle size of 400 μm as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1), mix well, and obtain mixture II for standby use; the purity of the NH4HCO3 powder used as a pore-forming agent is analytical grade, and the particle size is 400 μm;
[0058] (4) The stainless steel mold used in this step is the same as that in Example 1; the cushion block 6 is placed in the vertical cavity of the sleeve 3, the core rod 1 is inserted into the vertical cavity of the sleeve 3, and then the mixture I of step (2) is filled into the vertical cavity of the sleeve 3, the fixed cylinder 2 is inserted, and the mixture I therein is manually pressed to be pressed into an internal hollow cylinder, then the core rod 1 is pulled out, and the mixture II of step (3) is filled into the vertical cavity of the fixed cylinder 2, and the core rod 1 is inserted again, and the core rod 1 is manually pressed to compact the mixture II in the hollow cylinder, the core rod 1 and the fixed cylinder 2 are pulled out, and after the mold pressure rod 5 is inserted, it is sent to a conventional press, and the pressure is unidirectionally increased to 48 kN at a pressure rate of 3 kN / min, and the pressure is maintained for 28 minutes to complete the cold pressing molding, and then demolding is performed to obtain a cylindrical green body with a dense outer layer of the mixture I and a porous inner core of the mixture II;
[0059] (5) placing the cylindrical green body of step (4) into a tubular furnace, heating the temperature to 270° C. at a rate of 7° C. / min under a vacuum degree of 20 Pa and a continuous flow of 99.99% pure argon atmosphere, and keeping the temperature for 300 min to complete thermal debinding, and then cooling the green body to room temperature with the furnace for standby use;
[0060] (6) The cylinder that has been thermally degreased in step (5) is placed in a graphite mold, and then placed in a spark plasma sintering furnace. After evacuating to 4 Pa, the temperature is increased to 550°C at a heating rate of 80°C / min, and then increased to 900°C at a heating rate of 110°C / min. Finally, the temperature is increased to 1100°C at a heating rate of 50°C / min, and kept at this temperature for 9 minutes to complete the spark plasma sintering. The cylinder is then cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior. The graphite mold structure is the same as that in Example 1.
[0061] The dimensions of the cold pressed green body and the sintered sample were measured with a vernier caliper, and the shrinkage of the sample was obtained using a conventional calculation formula. The radial shrinkage and axial shrinkage of the Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and porous interior were 10.20% and 9.53% respectively.
[0062] The dense layer and the porous layer were cut into 3mm×3mm×3mm samples by electric spark wire cutting, and polished with 400-grit sandpaper to expose the surface with metallic luster. The density of the dense layer and the porosity of the porous layer were measured by Archimedes drainage method. The density of the dense layer of the surface of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior is 91.3%, and the porosity of the internal porous layer is 61.7%.
[0063] Table 1 shows the effect of sintering temperature of Examples 1, 2, and 3 on the density of the dense layer and the porosity of the porous layer of the medical titanium alloy with dense surface and porous interior;
[0064] Table 1
[0065]
[0066]
[0067] As can be seen from Table 1, the density of the surface dense layer of the medical titanium alloy materials with dense surface and porous interior is greater than 90%, and the porosity of the internal porous layer is about 60%, which belongs to the category of high porosity. Most of these pores are interconnected to form a network structure. This network structure can not only facilitate the ingrowth of bone cells and the formation of capillaries, but also play a role in stress release in the overall stress deformation of the material, so that the material can absorb more energy when deformed.
[0068] The mechanical properties of the material were tested for compression properties according to GB / T 31930-2015. In order to make the test statistically significant, the average value was taken after multiple tests. The test results are shown in Figure 5 The Ti6Al4V5Cu medical titanium alloy material with dense surface and porous interior has high compressive strength and low elastic modulus at the same time, with a compressive strength of 872MPa, a yield strength of 636.4MPa, and an elastic modulus of 13.8GPa, which matches the elastic modulus of human bones (2-30GPa). After implantation, the Ti6Al4V5Cu medical titanium alloy material has both load-bearing capacity and can disperse stress, reduce stress shielding, and is conducive to long-term and effective implantation.
[0069] Example 4
[0070] A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0071] (1) Using spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method as raw material, the particle size of which is 20 μm;
[0072] The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder is as follows: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;
[0073] (2) adding 6.54 g / ml of the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder, heating to 30° C., stirring and mixing to obtain a mixture I for standby use;
[0074] (3) Add 35% by mass of NH4HCO3 powder with a particle size of 500 μm as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1), mix well, and obtain mixture II for standby use; the purity of NH4HCO3 powder used as a pore-forming agent is analytical grade, and the particle size is 500 μm;
[0075] (4) The stainless steel mold used in this step is the same as that in Example 1; the cushion block 6 is placed in the vertical cavity of the sleeve 3, the core rod 1 is inserted into the vertical cavity of the sleeve 3, and then the mixture I of step (2) is filled into the vertical cavity of the sleeve 3, the fixed cylinder 2 is inserted, and the mixture I inside is pressed manually to be pressed into a hollow cylinder inside, then the core rod 1 is pulled out, and the mixture II of step (3) is filled into the vertical cavity of the fixed cylinder 2, and the core rod 1 is inserted again, and the core rod 1 is pressed manually to compact the mixture II into the hollow cylinder, the core rod 1 and the fixed cylinder 2 are pulled out, and the mold pressure rod 5 is inserted, and then sent to a conventional press, and unidirectionally pressurized to 48 kN at a pressurization rate of 2 kN / min, and the pressure is maintained for 27 minutes to complete the cold pressing molding, and then demolded to obtain a cylindrical green body with a dense outer layer of the mixture I and a porous inner core of the mixture II;
[0076] (5) placing the cylindrical green body of step (4) into a tubular furnace, heating the body to 250° C. at a rate of 5° C. / min under a vacuum degree of 25 Pa and a continuous flow of argon gas with a purity of 99.99%, maintaining the temperature for 270 min to complete thermal debinding, and then cooling the body to room temperature with the furnace for standby use;
[0077] (6) The cylinder that has been thermally degreased in step (5) is placed in a graphite mold, and then placed in a spark plasma sintering furnace. After evacuating to 5 Pa, the temperature is increased to 580° C. at a heating rate of 85° C. / min, and then increased to 880° C. at a heating rate of 96° C. / min. Finally, the temperature is increased to 1150° C. at a heating rate of 47° C. / min. The temperature is kept at this temperature for 10 min to complete the spark plasma sintering, and then the cylinder is cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior. The graphite mold structure is the same as that in Example 1.
[0078] The dense layer and the porous layer were cut into 3mm×3mm×3mm samples by electric spark wire cutting, and polished with 400 mesh sandpaper to expose the surface with metallic luster. The density of the dense layer and the porosity of the porous layer were measured according to the Archimedes drainage method. The density of the dense layer on the surface of the Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and porous interior was 92.3%, and the porosity of the internal porous layer was 53.2%.
[0079] The mechanical properties of the material were tested for compression properties according to GB / T 31930-2015. In order to make the test statistically significant, the average value was taken after multiple tests. The test results are shown in Figure 6 The Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior has high compressive strength and low elastic modulus. The compressive strength is 1079.1MPa, the yield strength is 769.1MPa, and the elastic modulus is 14.8GPa, which has an elastic modulus matching that of human bone (2-30GPa). After implantation, the Ti6Al4V5Cu medical titanium alloy material has both load-bearing capacity and can disperse stress, reduce stress shielding, and is conducive to long-term and effective implantation.
[0080] Example 5
[0081] A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized by comprising the following steps:
[0082] (1) Using spherical Ti6Al4V5Cu titanium alloy powder prepared by electrode induction melting inert gas atomization method as raw material, the particle size of which is 20 μm;
[0083] The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder is as follows: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;
[0084] (2) adding 6.54 g / ml of the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder, heating to 30° C., stirring and mixing to obtain a mixture I for standby use;
[0085] (3) Add 45% by mass of NH4HCO3 powder with a particle size of 500 μm as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder of step (1), mix well, and obtain mixture II for standby use; the purity of the NH4HCO3 powder used as a pore-forming agent is analytical grade, and the particle size is 500 μm;
[0086] (4) The stainless steel mold used in this step is the same as that in Example 1; the cushion block 6 is placed in the vertical cavity of the sleeve 3, the core rod 1 is inserted into the vertical cavity of the sleeve 3, and then the mixture I of step (2) is filled into the vertical cavity of the sleeve 3, the fixed cylinder 2 is inserted, and the mixture I therein is pressed manually to be pressed into an internal hollow cylinder, then the core rod 1 is pulled out, and the mixture II of step (3) is filled into the vertical cavity of the fixed cylinder 2, and the core rod 1 is inserted again, and the core rod 1 is pressed manually to compact the mixture II into the hollow cylinder, the core rod 1 and the fixed cylinder 2 are pulled out, and after the mold pressure rod 5 is inserted, it is sent to a conventional press, and unidirectional pressure is applied to 46 kN at a pressure rate of 1 kN / min, and the pressure is maintained for 29 minutes to complete the cold pressing molding, and then demolding is performed to obtain a cylindrical green body with a dense outer layer of the mixture I and a porous inner core of the mixture II;
[0087] (5) placing the cylindrical green body of step (4) into a tubular furnace, heating the body to 270° C. at a rate of 7° C. / min under a vacuum degree of 20 Pa and a continuous flow of 99.99% pure argon atmosphere, and maintaining the temperature for 260 min to complete thermal debinding, followed by cooling to room temperature in the furnace for standby use;
[0088] (6) The cylinder that has been thermally degreased in step (5) is placed in a graphite mold, and then placed in a spark plasma sintering furnace. After evacuating to 6 Pa, the temperature is increased to 560° C. at a heating rate of 82° C. / min, and then increased to 890° C. at a heating rate of 110° C. / min. Finally, the temperature is increased to 1150° C. at a heating rate of 48° C. / min. The temperature is kept at this temperature for 10 min to complete the spark plasma sintering, and then the cylinder is cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy cylinder with a dense surface and a porous interior. The graphite mold structure is the same as that in Example 1.
[0089] The dense layer and the porous layer were cut into 3mm×3mm×3mm samples by electric spark wire cutting, and polished with 400 mesh sandpaper to expose the surface with metallic luster. The density of the dense layer and the porosity of the porous layer were measured according to the Archimedes drainage method. The density of the surface dense layer of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior was 92.6%, and the porosity of the internal porous layer was 65.3%.
[0090] Table 2 shows the effect of the mass fraction of ammonium bicarbonate on the porosity of the porous layer of the medical titanium alloy with dense surface and porous interior in Examples 2, 4, and 5;
[0091] Table 2
[0092] Ammonium bicarbonate mass fraction (wt%) 35 40 45 Porosity (%) 53.2% 61.0% 65.3%
[0093] The mechanical properties of the material were tested for compression properties according to GB / T 31930-2015. In order to make the test statistically significant, the average value was taken after multiple tests. The test results are shown in Figure 6 , it can be seen that with the increase of the content of the internal pore-forming agent, the compressive strength and elastic modulus of the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior show a downward trend. When the mass fraction of the pore-forming agent content is 45%, the Ti6Al4V5Cu medical titanium alloy cylinder with dense surface and porous interior has a low elastic modulus while having high compressive strength, a compressive strength of 984.1MPa, a yield strength of 744.6MPa, and an elastic modulus of 14.1GPa, which matches the elastic modulus of human bones (2-30GPa). After implantation, the Ti6Al4V5Cu medical titanium alloy material has both load-bearing capacity and can disperse stress, reduce stress shielding, and is conducive to long-term effective implantation.
[0094] In summary, the medical titanium alloy with a dense surface and porous interior prepared by the present invention has high compressive strength (≥872MPa) and low elastic modulus (≤16GPa), and the interior of the medical titanium alloy with a dense surface and porous interior presents a porous structure interconnected with each other (porosity of 50% to 68%), which can not only promote the growth of bone tissue, but also release stress and buffer motion loads when the material is deformed as a whole; at the same time, copper ions and body fluids can be transmitted between the internal porous structure and bone tissue, giving the alloy a certain antibacterial property.
[0095] The above description is only a preferred implementation manner of the present invention, but the protection scope of the present invention is not limited thereto, and any modification and replacement based on the technical solution and inventive concept provided by the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a medical titanium alloy with a dense surface and porous interior, characterized in that The following steps are included: (1) Spherical Ti6Al4V5Cu titanium alloy powder with a particle size of 10~20μm is used as raw material; (2) Add the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) to liquid paraffin as a binder in an amount of 6.13-6.54 g / ml, heat to 20-30° C., stir and mix evenly to obtain a mixture I, which is set aside; (3) Add NH4HCO3 powder with a particle size of 300-500 μm and used as a pore-forming agent to the spherical Ti6Al4V5Cu titanium alloy powder prepared in step (1) at a mass ratio of 35-45%, mix well, and obtain mixture II for standby use; (4) Filling the mixture I of step (2) into a stainless steel mold and pressing it into a hollow cylinder, then filling the hollow cylinder with the mixture II of step (3), cold pressing and removing the mold to obtain a green body with the outer layer of the mixture I and the inner layer of the mixture II; (5) placing the green body of step (4) into a tubular furnace, heating the body to 200-300°C at a rate of 4-8°C / min under the conditions of a vacuum degree of 10-25 Pa and a continuous flow of argon gas with a purity of 99.99%, keeping the temperature for 240-300 min to complete thermal debinding, and then cooling the body to room temperature with the furnace for standby use; (6) The green body after hot degreasing in step (5) is placed in a graphite mold, placed in a spark plasma sintering furnace, evacuated to 4-6 Pa, heated to 550-650°C at a heating rate of 80-90°C / min, then heated to 850-900°C at a heating rate of 90-110°C / min, and finally heated to 1100-1200°C at a heating rate of 40-50°C / min, kept at this temperature for 8-12 min to complete spark plasma sintering, and then cooled to room temperature with the furnace to obtain a Ti6Al4V5Cu medical titanium alloy with a dense surface and porous interior.
2. The method for preparing a medical titanium alloy with a dense surface and porous interior according to claim 1, characterized in that: The chemical composition of the spherical Ti6Al4V5Cu titanium alloy powder in step (1) is as follows: Al: 5.50-6.50wt.%, V: 3.50-4.50wt.%, Cu: 4.50-6.0wt.%, Fe: ≤0.25wt.%, C: ≤0.08wt.%, N: ≤0.03wt.%, H: ≤0.008wt.%, O: ≤0.13wt.%, and the remainder is Ti.
3. The method for preparing a medical titanium alloy with a dense surface and porous interior according to claim 1, characterized in that: The spherical Ti6Al4V5Cu titanium alloy powder in step (1) is prepared by electrode induction melting and inert gas atomization.
4. The method for preparing a medical titanium alloy with a dense surface and porous interior according to claim 1, characterized in that: The pressing process of step (4) is unidirectional pressing, the pressing rate is 1-3 kN / min, the pressure is 45-50 kN, and the holding time is 25-30 min.
Citation Information
Patent Citations
Preparation method of antibacterial functional gradient porous HA-Ag bone filling scaffold with active interlayer
CN106312050A
Preparation method of titanium base biomedical gradient composite material
CN108380891A
Preparation method for medical antibacterial titanium alloy
CN109055814A
Tantalum powder for medical porous skeletons as well as preparation method and application of tantalum powder
CN113263179A
Process for preparing a sintered article having a compact outer layer and a smooth surface
EP0446673A1